Chemical-Shift-Encoded Magnetic Resonance Imaging and Spectroscopy to Reveal Immediate and Long-Term Multi-Organs Composition Changes of a 14-Days Periodic Fasting Intervention: A Technological and Case Report - Viallon, Magalie; Leporq, Benjamin; Drinda, Stephan; Wilhelmi de Toledo, Françoise; Galusca, Bogdan; Ratiney, Helene; Croisille, Pierre (Frontiers in Nutrition, 2019)
Objectives: The aim of this study was to investigate the feasibility of measuring the effects of 14-days low-calory-diet (<200cal) on multi-organs of main interest (liver, visceral/subcutaneous/bone marrow fat, muscle) using non-invasive advanced spectroscopic moreover magnetic resonance imaging (MRI) methods. Methods: One subject participated in a 14-day fast under daily supervision of nurses and specialized physicians, ingesting a highly reduced intake: 180 Kcal/day coupled with active walking and at least drinking 3l of water/day. The fasting was preceded by a 7-days pre fasting vegetarian period and followed by 14 days of a stepwise reintroduction of food. The longitudinal study collected imaging and biological data before, at peak fasting, 7 days after re-feeding 1month and 4 months after. Body fat mass in trunk, abdomen, and thigh, liver and muscle mass, were respectively computed using advanced MRI and MRS signal modeling. Fat fraction, MRI relaxivity index T2* and susceptibility (Chi), as well as Fatty acid composition, were calculated at all time points. Results: A decrease in body weight (BW:-9.5%), quadriceps muscle volume (-3.2%), Subcutaneous and Visceral Adipose Tissue (SAT -34.4%; VAT -20.8%), liver fat fraction (PDFF = 1.4 % vs. 2.6 % at baseline) but increase in Spine Bone Marrow adipose tissue (BMAT) associated with a 10% increase in global adiposity fraction (PDFF: 54.4% vs. 50.9 %) was observed. Femoral BMAT showed minimal changes compared to spinal level, with a slight decrease (-3.1%). Interestingly, fatty acid (FA) pattern changes differed depending on the AT locations. In muscle, all lipids were increased after fasting, with a greater increase of intramyocellular lipid (IMCL: from 2.7 to 6.3mmol/kg) after fasting compared to extramyocellular lipid ( EMCL: from 6.2 to 9.5mmol/kg) as well as Carnosine (6.9 to 8.1mmol/kg). Heterogenous and reverse changes were also observed after re-feeding depending on the organ.